On the valuation of economic goods - Giza, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2019)
The presented study includes an analysis of the category of “good” on the basis of philosophy and economics. Particular attention was paid here to the factors determining the monetary value (price) of an economic good. While achieving the assumed objective of the research, answers to the following questions were sought: What is the difference, therefore, in the interpretation of good as an axiological category and good which economics deals with? What is the basis for the valuation of goods which are the subject of economic analysis? While seeking answers to these questions, an attempt was made to justify the thesis according to which contemporary understanding of the way the market valuates goods is limited to accepting the price understood as a variable representing a kind of relationship set in a given time period.